2016
DOI: 10.1177/0004865816655588
|View full text |Cite
|
Sign up to set email alerts
|

Examining forensic interviewers’ perceptions of practice-focused supervision

Abstract: Regular supervision influences interviewing quality with child witnesses. It is unclear, however, whether interviewers recognize the importance of supervision, and how often they access it. The present study surveyed 39 New Zealand Specialist Child Witness Interviewers (otherwise known as forensic interviewers), and examined: (a) their access to, and, perceptions of supervision, and (b) factors that may influence their access to, and, perceptions of supervision. We identified 26 interviewers who received some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…We saw variations in questioning across and within groups, even though the interviewers were well trained and had access to frequent supervision and fidelity monitoring. Field studies have shown that access to supervision is associated with better interviewing quality (Lamb, 2016;Lamb, Sternberg, Orbach, Esplin, et al, 2002;Wolfman, Brown, & Jose, 2016c) and so our results may paint a more optimistic picture than would be seen in the field where interviewers may have difficulty obtaining regular feedback about their work (Wolfman et al, 2016c).…”
Section: Discussionmentioning
confidence: 73%
“…We saw variations in questioning across and within groups, even though the interviewers were well trained and had access to frequent supervision and fidelity monitoring. Field studies have shown that access to supervision is associated with better interviewing quality (Lamb, 2016;Lamb, Sternberg, Orbach, Esplin, et al, 2002;Wolfman, Brown, & Jose, 2016c) and so our results may paint a more optimistic picture than would be seen in the field where interviewers may have difficulty obtaining regular feedback about their work (Wolfman et al, 2016c).…”
Section: Discussionmentioning
confidence: 73%
“…This may have been due to work pressure, access to computers or potentially a reluctance for their practice to be analysed. Despite this attrition rate, we had a similar rate of participation to other studies (Wolfman et al, 2016a;Wright & Powell, 2006), but a challenge remains for researchers as to how to increase engagement and participation with studies involving forensic interviewers.…”
Section: Limitationsmentioning
confidence: 81%
“…Regular supervision and feedback focused on interviewing practice has been shown to significantly contribute to the adherence of best practice interviewing (Cyr, Dion, McDuff & Trotier-Sylvain, 2012;Wolfman, Brown & Jose, 2016a). No significant differences were found between the frequency of supervision and the amount of interviewers' knowledge of research.…”
Section: Interviewers' Knowledge Of Research Evaluating Visual Aids and Its Relevance Tomentioning
confidence: 99%
“…given the probability interviewers' self-report may be inaccurate, and the likelihood they may be overestimating their use of open questions and underestimating their use of closed (Wolfman, Brown & Jose, 2015;Wolfman, Brown & Jose, 2016a). These results therefore may be the result of two factors; interviewers subjectively overestimating their use of good questioning, or the positive impact of recent initiatives.…”
Section: Interviewers' Perspectives On Visual Aids 60mentioning
confidence: 99%
See 1 more Smart Citation